2012
DOI: 10.1524/zpch.2012.0250
|View full text |Cite
|
Sign up to set email alerts
|

Li Ion Dynamics in Al-Doped Garnet-Type Li7La3Zr2O12 Crystallizing with Cubic Symmetry

Abstract: Lithium-ion dynamics in the garnet-type solid electrolyte "Li 7 La 3 Zr 2 O 12 " (LLZ) crystallizing with cubic symmetry was probed by means of variable-temperature 7 Li NMR spectroscopy and ac impedance measurements. Li jump rates of an Al-containing sample follow Arrhenius behavior being characterized by a relatively high activation energy of 0.54(3) eV and a pre-exponential factor of 2.2(5) × 10 13 s −1 . The results resemble those which were quite recently obtained for an Al-free LLZ sample crystallizing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…By reducing the Li content, Li vacancies are created and together with the introduction of the Al substituent, these two chemical modifications play a major role in the Li-ion conduction mechanism, and not only the crystalline structure. A purely cubic LLZ is not necessary for achieving high total Li-ion conductivity as shown here and as there exist also examples of poorly conductive cubic LLZ [31]. Nevertheless, from the ICP-OES results, there is definitely more Li in the samples than what is needed for stoichiometric LLZ:Al if we assume Al 3+ only replacing Li + sites.…”
Section: Resultsmentioning
confidence: 72%
“…By reducing the Li content, Li vacancies are created and together with the introduction of the Al substituent, these two chemical modifications play a major role in the Li-ion conduction mechanism, and not only the crystalline structure. A purely cubic LLZ is not necessary for achieving high total Li-ion conductivity as shown here and as there exist also examples of poorly conductive cubic LLZ [31]. Nevertheless, from the ICP-OES results, there is definitely more Li in the samples than what is needed for stoichiometric LLZ:Al if we assume Al 3+ only replacing Li + sites.…”
Section: Resultsmentioning
confidence: 72%
“…In the laboratory frame, an absolute lithium jump rate can be deduced from the maximum condition τ·ω o ≈ 1 which is valid at the maximum relaxation rate. 28 From Figure 5b, it is observed that the maximum SLR rate is reached at 333 K for SSM-Li 6 PS 5 Cl and at 345 K for BMA-Li 6 PS 5 Cl. This corresponds to the same lithium jump frequency (9.80 × 10 8 s –1 ) calculated based on the above-described maximum 1/ T 1 relaxation condition.…”
Section: Resultsmentioning
confidence: 84%
“…7 Li NMR spin-lattice relaxation (SLR) rates R 1 in the laboratory frame of reference were acquired by means of the classical saturation recovery pulse sequence 10 Â p/2 À t d À p/2 À acquisition (acq.) [38][39][40][41][42] The initial ten p/2 pulses in rapid succession are used to destroy any longitudinal magnetization M z . Immediately aer this saturation comb, the recovery of M z is recorded as a function of delay time t d at different temperatures.…”
Section: B Characterization Of Ion Transport and LI Diffusivitymentioning
confidence: 99%